Protestantism, post-colonialism and Israel – 1948–1967 - van Klinken, Geert Johannes (Stellenbosch Theological Journal, 2024)
In this contribution, Protestant interaction with the State of Israel is analysed within the framework of the aftermath of Modern Imperialism between 1850 and 1950. It was the time when Western European nations expanded into areas previously inhabited by others, where they established white settlers’ communities as the political and economic dominant in the USA, Australia, New Zealand, South Africa and elsewhere. The genesis of the State of Israel in 1948 can be seen as a late example of the same phenomenon. Very soon after 1948 however, most Protestant churches would become aware of the importance of post-colonialism and a new global world order, where the West was no longer dominant and issues of land ownership in the former (semi-)colonies became important. This implied an overhaul of the idea, still current among Protestants in the 1950s, that the population exchanges in former Palestine in 1948 needed to be accepted both as a cultural advance and as an outcome of Bible exegesis.